UMPSA expands its partnership network with Gebeng Industries - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
KUANTAN, 9 October 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is broadening its collaboration network with industries in Gebeng to establish partnerships with industry peers in mutually agreed fields alongside the university.